白令海表层营养盐水平输送的镭-228示踪 - 邢娜; 陈敏; 黄奕普; 邱雨生 (2011)
对白令海表层海水228rA的分析表明,白令海表层海水228rA比活度从低于检测限变化至0.81 bQ/M3,低于西北冰洋陆架区的报道值。表层水228rA比活度和228rA/226rA)A.r.的空间分布均呈现由西南部中心海盆向东北部陆架区增加的趋势。由228rA/226rA)A.r.和盐度的关系揭示出白令海环流、白令海陆坡流和阿拉斯加沿岸流对228rA和228rA/226rA)A.r.分布有明显影响。运用一维稳态扩散模型计算出白令海由中心海盆向东北部陆架方向上水体混合的水平涡动扩散系数为1.9x108M2/d。结合海盆-陆架界面营养盐的水平浓度梯度,估算得硝酸盐、活性磷酸盐和活性硅酸盐由白令海中心海盆向东北部陆架区的水平输送通量,该通量对白令海东北部陆架区新生产力的贡献很小,其他途径输送的营养盐更为重要。 Surface water in the Bering Sea was collected in July-September 1999 for 228Ra measurements and used as a tracer for the cross-shelf exchange of nutrients.The specific activity of surface 228Ra ranges from below detection to 0.81 Bq/m3,which is lower than that reported in the western shelves of the Arctic Ocean.The spatial distribution of 228Ra and 228Ra/226Ra)A.R.shows an increase from the central basin to the northeastern shelf.The relationship between 228Ra/226Ra)A.R.and salinity indicates the influence of the Bering gyre,the Bering Slope Current and the Alaska Coastal Current on 228Ra and 228Ra/226Ra)A.R.Based on a one-dimensional steady state model of 228Ra,the horizontal eddy diffusion coefficient in study areas was calculated to be 1.9×108 m2/d.The horizontal exchange fluxes of nutrients from the central basin to the northeastern shelf were estimated by combining the horizontal eddy diffusion coefficient and the spatial gradients of nutrients.The surface horizontal input of nitrate to the northeastern shelf only contributed a small fraction to the new production in the northeastern Bering Sea shelf waters,indicating the importance of other nutrient input pathways in supporting new production on the northeastern Bering shelf. 国际极地年中国行动计划项目;中国第三次北极科学考察资助项目;福建省自然科学基金杰出青年基金项目(2009J06026)